Direct Air Capture of CO2 by Physisorbent Materials. (6th October 2015) - Kumar, Amrit; Madden, David G.; Lusi, Matteo; Chen, Kai‐Jie; Daniels, Emma A.; Curtin, Teresa; Perry, John J.; Zaworotko, Michael J.
Abstract: Sequestration of CO2, either from gas mixtures or directly from air (direct air capture, DAC), could mitigate carbon emissions. Here five materials are investigated for their ability to adsorb CO2 directly from air and other gas mixtures. The sorbents studied are benchmark materials that encompass four types of porous material, one chemisorbent, TEPA‐SBA‐15 (amine‐modified mesoporous silica) and four physisorbents:Zeolite 13X (inorganic);HKUST‐1 andMg‐MOF‐74/Mg‐dobdc (metal–organic frameworks, MOFs);SIFSIX‐3‐Ni, (hybrid ultramicroporous material). Temperature‐programmed desorption (TPD) experiments afforded information about the contents of each sorbent under equilibrium conditions and their ease of recycling. Accelerated stability tests addressed projected shelf‐life of the five sorbents. The four physisorbents were found to be capable of carbon capture from CO2 ‐rich gas mixtures, but competition and reaction with atmospheric moisture significantly reduced their DAC performance.